Fluorescence recognition of adenosine triphosphate and uric acid by two Eu-based metal–organic frameworks. Issue 18 (28th April 2021) - Han, Li-Juan; Kong, Ya-Jie; Zhang, Xing-Min; Hou, Guo-Zheng; Chen, Hua-Chong; Zheng, He-Gen
Abstract : Two Eu-based MOF fluorescent sensors were synthesized and they exhibited excellent recognition abilities for adenosine triphosphate (ATP) and uric acid (UA). Abstract : Two Eu-based MOF fluorescent sensors, Eu2 (CHDA)2 (C2 O4 )(H2 O)4 (1 ) (CHDA = 1, 4-cyclohexanedicarboxylic acid, C2 O4 = oxalate group) and Eu2 (PDA)3 (H2 O)3 (2 ) ( p -phenylenediacetic acid = PDA), were prepared for the rapid detection of uric acid (UA) and adenosine triphosphate (ATP). The properties of the sensors were elucidated using photoluminescence spectrosopy and UV-vis absorption spectroscopy. The results reveal that compound 1 suspension can selectively recognize ATP by fluorescence quenching, and compound 2 suspension exhibits a special selectivity for UA, all of which are due to the spectral overlap and energy competition and transfer. The two MOF-based sensors feature high quenching efficiencies K sv (5.49 × 10 4 M −1 for ATP; 1.14 × 10 4 M −1 for UA), low detection limits (ATP: 0.490 μM; UA: 0.601 μM) and fast response times (in seconds). Accordingly, the excellent selectivity and sensitivity for ATP and UA can be realized by a "turn-off" fluorescence response. In addition, the two fluorescent MOFs can also enable the fabrication of test strips, which provided a low cost, simple and flexible way to detect trace amounts of UA and ATP in aqueous solutions or organisms. This work provides new perspectives for the development of rare-earth MOFs in detecting uric acid and adenosine triphosphate, possessing the potential for possible applications in real-life scenarios.